Interplay of inlet temperature and humidity on energy penalty for CO2 post-combustion capture: Rigorous analysis and simulation of a single stage gas permeation process. (1st December 2016) - Giordano, Lorena; Roizard, Denis; Bounaceur, Roda; Favre, Eric
Abstract: Over the last decade, membrane separation processes have attracted considerable research attention. This is due to their potential for lowering the costs of post-combustion CO2 capture compared with the more established technologies, which are based on the use of chemical solvents. It is well known that the performance of membrane-based CO2 capture is related to several factors, including flue gas composition, membrane material and system design. Membrane working temperature is one of the operating parameters that have several implications on the CO2 separation process. However, surprisingly, this key operating variable has not been investigated in detail. It not only influences the intrinsic membrane properties and the feed composition but also indirectly affects the energy behavior of the whole capture system. Hence, the resulting outcome cannot be intuitively deduced. In this work the combined effect of operating temperature and humidity on a CO2 capture process has been deeply investigated, focusing on a single stage membrane unit with feed compression and permeate vacuum pumping. Considering as case study the flue gas from a coal-fired power plant, the paper assesses the variation in separation performances with respect to CO2 permeate purity and membrane area. The variation of energy expenses of membrane system with respect to two types of polymeric membranes (Polyactive™1500, PIM-1), which have different gas separation properties (permeability, selectivity), has also been evaluated. This study reveals that an increase in the membrane operating temperature from 30 °C to 70 °C negatively affects CO2 permeate purity, losing more than 10% pts irrespective of capture ratio. Conversely, the influence on area requirement is strictly related to the type of membrane material. Additionally the specific energy requirement to drive the separation process increases, ranging from around 250 kWh/tonne (Polyactive™1500) to 290 kWh/tonne (PIM-1) for a separation degree of 90%. Highlights: The interplay between temperature, humidity and pressure ratio is investigated. A lower membrane temperature decreases the overall energy requirement. A minimum energy requirement of 1.5 GJ/ton is achievable. The increase of membrane temperature negatively affects CO2 permeate purity. Effect of temperature on surface area depends on the type of membrane material.